NEUROINTERVENSI PENATALAKSANAAN STROKE ISKEMIK FASE AKUT TERKINI ULASAN SINGKAT STUDI MR CLEAN ESCAPE EXTENDIA DAN SWIFT PRIME - Fritz Sumantri Usman* (NEURONA, 2016)
DEVELOPMENT OF THERAPEUTIC MANAGEMENT OF ACUTE ISCHEMIC STROKE IS DYNAMIC AND IMPROVING SEVERAL LARGE STUDIES SUCH AS MR CLEAN ESCAPE EXTEND IA AND SWIFT PRIME SHOWED A HIGHLY SIGNIFICANT IMPROVEMENT RESULTS IN THE ACUTE PHASE OF ISCHEMIC STROKE THESE STUDIES COMBINED TWO METHODS OF THROMBOLYSIS INTRAARTERIAL OR INTRAVENOUS FOLLOWED BY THROMBECTOMY